Efek pemberian ekstrak ethanol ubi jalar ungu (Ipomoea batatas L) terhadap ketebalan dan diferensiasi sel epitel vagina tikus betina yang mengalami ovariektomi di Laboratorium Histologi Fakultas Kedokteran Universitas Udayana periode Oktober-Desember 2017 - Yuwono, Jessica; Sugiritama, Wayan; Mayun, Gusti Ngurah; Sumadi, Wayan Juli (E-Jurnal Medika Udayana; Vol 7 No 5 (2018): E-Jurnal Medika Udayana, 2018)
Post menopause woman experiencing estrogen hormone deficiency causing vaginal atrophy leading decrease in vaginal epithelial thickness. Hormone replacement therapy (HRT) was the first choice to overcome those problems. Meanwhile, HRT has so much adverse effect in long term use such as increase risk of breast cancer, and cardiovascular disease. Phytoestrogen is an estrogen compound derived from plant particullary in purple yam, containing antosianin that could be an alternative for estrogen replacement therapy. Study design is post-test only control group with animal model using wistar mice divided into four groups intervention. Control group recieving placebo, intervention group 1 (I1) recieving 1 cc of purple yam ethanol extract, I2 and I3 recieving 2cc and 4 cc of yam ethanol extract respectively. Oovorectomy was done before intervention and intervention was done for one months. Histophatological structure of vaginal epithelial and assesment of vaginal epithelial maturation was observed. There are significant difference between the average number of parabasal cell, intermediate cell, and superficial cell in four groups intervention (p=0.000). The highest number of parabasal cell was found in control group (151.63±34.13), the highest number of intermediate cell was found in I3 group, and the highest number of superficial cell was found in I3 group. There are significant different between thickness of epithelial cell layer in four groups intervention (p=0.004) and I3 group with the thickest layer of ephitel (54.24 ± 7.782). The best maturation degree was found in I3 group with much squamous epithelium with thick layer of glicogen on the surface of epithelial layer. Meanwhile, control group was found with poor maturation, superficial epithelial layer undergoes keratinization with predominant of parabasal cell layer and only a few number of superficial squamous epithelial cell was found. Intervention of purple yam ethanol extract enhance epithelial maturation and differentiation, increase epithelial thickness in rats undergoes oovorectomy. Keywords: purple yam extract, vagina epithelial, thickness of epithelial, maturation degree, phytoestrogen.